Comparison of Financial Stability of the Russian and Mongolian Regions Based on System of National Accounts - Zakharchuk, Yekaterina Aleksandrovna; Pasynkov, Aleksey Fedorovich (Economy of Regions, 2015)
The main purpose of the article is a comparative evaluation of the financial stability of the territories of Mongolia and the Russian Federation in the ongoing international research on the dynamics determination of the socio-economic development of both countries. In the study, the attempt to compound the existing data sources of regional development of the Russian Federation and Mongolia in uniform system for comparative evaluation of financial stability of territories on the basis of the methodology of the System of National Accounts is made. The author’s approach to build and fill the balances of the movement of financial resources in the regions by sectors of «Corporation», «Public Administration» and «Household» is presented. The comparative characteristics of socio-economic development in the context of 21 aimaks and the capital of Mongolia - Ulan Bator, and five border regions of Russia (Republic of Altai, Tuva, Buryatia, Khakassia and the Trans-Baikal Territory, as well as enlarged «macro-regions» (Mongolia as a whole, the border areas Russia together and Sverdlovsk region) are determined. The analysis of the gross regional product structure of these regions is carried out. It has revealed the agricultural specialization of Mongolian regions and domination of service sector and public management in the development of added value in the Russian territories. Also, the identified features of the distribution of value added in the sector «corporation» in both countries lying in the different structural relations of SNA indicators are discovered. Investigation of the flow of financial resources for the «Governance» sector led to the conclusion of a more balanced ratio of own income and expenditure budgets of the regions of Mongolia than the border regions of the Russian Federation. As a result, in the entire set of selected areas were identified with common features and regularities of their financial development in the context of economic sectors, the main findings and development schemes of financial stability of the Russian Federation and Mongolia are presented.